Efektivitas Pelayanan Padang Command Center (PCC) 112 dalam Mendukung Program Smart City di Kota Padang - Anjel Anjel; M. Fachri Adnan (Al-DYAS, 2026)
The development of the smart city concept encourages local governments to provide public services that are more responsive, integrated, and information technology-based. Padang City has operated Padang Command Center (PCC) 112 as an integrated emergency service center that connects the public with various government agencies in real time. However, the effectiveness of PCC 112 services in supporting smart city governance still needs to be examined empirically because its success depends heavily on response quality, timeliness, and public satisfaction as service users. This study aimed to analyze the effectiveness of PCC 112 services in terms of institutional aspects, resources, and the achievement of public service objectives within the smart city framework. This study used a descriptive qualitative approach. Data were collected through in-depth interviews with operators, relevant officials, and community members who used the service, as well as documentation studies of performance reports and applicable regulations. The results showed that PCC 112 had successfully integrated various complaint channels and emergency services into a single integrated platform with a relatively rapid response time. However, service effectiveness still faced several challenges, including limited trained human resources, technological infrastructure that was not yet fully optimal, varying levels of public digital literacy, and service socialization that had not been evenly distributed across all areas of the city. The conclusion of this study emphasizes that PCC 112 has demonstrated fairly good effectiveness in supporting the implementation of a smart city in Padang City, but it still requires strengthening institutional capacity, improving digital infrastructure, and expanding socialization continuously so that the service can operate more optimally and provide broader impacts for the community.